Analisis Profitabilitas, Solvabilitas dan Ukuran Perusahaan yang Menyebabkan Audit Delay - Lala Febby Ardiany; R. Deni Muhammad Danial; Dicky Jhoansyah (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study is to determine the ratio of profitability, solvency and size of the company whether it affects the Audit Delay on PT Apexindo Pratama Duta Tbk listed on the Stock Exchange in the 2015-2017 period. the analytical method used in this research is descriptive-associative method. The data used in this study are secondary data from the company's financial statements. The results showed the value of Nagelkerke R Square was 0.672. This value shows the ability of independent variables (profitability, solvency and company size) in explaining the dependent variable (Audit Delay) is 67.2% and the remaining 32.8% there are other factors outside the model that explain the dependent variable. And the results of the Omnibus Test of Model Coefficients with a value of 0.329, which means greater than 0.05, the profitability, solvency and size of the company variables together do not affect the company's model (Audit Delay). In conclusion, profitability, solvency and company size variables do not affect and cause Audit Delay at PT Apexindo Pratama Duta Tbk. Keywords: Audit Delay, Company’s Measurement, Profitability Ratio Solvability Ratio,